Pendampingan UMKM dalam Promosi dan Pengelolaan Keuangan untuk Meningkatkan Daya Saing ABG Sawahan Catering : Penelitian - Sesti Anggi Fatmala; Wislla Febrianti; Abdul Majid (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the national economy, yet they still face numerous challenges in enhancing their competitiveness, particularly in promotion and financial management. ABG Sawahan Catering, a culinary business in Lamongan, has significant growth potential, but has yet to fully utilize digital promotional strategies and implement a financial recording system. This community service program aims to provide assistance to MSMEs in enhancing their digital-based promotional strategies and improving their financial management to enhance their competitiveness and business profitability. The methods applied included direct observation, interviews with business owners, and face-to-face mentoring focused on utilizing social media as a promotional tool and training in simple financial record-keeping, including recording income, expenses, and calculating the Cost of Goods Sold (COGS) using the full costing method. The results of this program showed an increase in business owners' understanding of the importance of digital marketing and sound financial management. Partners began to be able to manage social media in a more planned manner and understand the relationship between production costs, selling prices, and business profits. This mentoring is expected to improve operational efficiency and the competitiveness of MSMEs.